2002
DOI: 10.1142/s0217979202013420
|View full text |Cite
|
Sign up to set email alerts
|

HIGH PRESSURE TRANSPORT STUDY OF NON-FERMI LIQUID BEHAVIOUR IN U2Pt2In AND U3Ni3Sn4

Abstract: The strongly correlated metals U2Pt2In and U3Ni3Sn4 show pronounced non-Fermi liquid (NFL) phenomena at ambient pressure. Here we review single-crystal electrical resistivity measurements under pressure ( p ≤ 1.8 GPa) conducted to investigate the stability of the NFL phase. For tetragonal U2Pt2In (I || a) we observe a rapid recovery of the Fermi-liquid T 2 -term with pressure. The Fermi-liquid temperature varies as TFL ~ p-pc, where pc= 0 is a critical pressure. The analysis within the magnetotransport theory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…U 3 Ni 3 Sn 4 is described as a heavy-fermion paramagnet located at the verge of the antiferromagnetic quantum critical point with the negative critical pressure of −0.04 GPa. 12,[16][17][18] From low-temperature specific heat measurements, it is suggested that the crossover from the non-Fermi liquid to the Fermi liquid state occurs below 0.4 K. 13) Upon applying pressure, the Fermi liquid state is recovered in a wide tempera-ture range. 16) A photoemission study by Takabatake et al indicated that hybridization of the partially filled Ni 3d bands with the U 5 f states may lead to the delocalization of the 5 f electrons in U 3 Ni 3 Sn 4 .…”
Section: Introductionmentioning
confidence: 99%
“…U 3 Ni 3 Sn 4 is described as a heavy-fermion paramagnet located at the verge of the antiferromagnetic quantum critical point with the negative critical pressure of −0.04 GPa. 12,[16][17][18] From low-temperature specific heat measurements, it is suggested that the crossover from the non-Fermi liquid to the Fermi liquid state occurs below 0.4 K. 13) Upon applying pressure, the Fermi liquid state is recovered in a wide tempera-ture range. 16) A photoemission study by Takabatake et al indicated that hybridization of the partially filled Ni 3d bands with the U 5 f states may lead to the delocalization of the 5 f electrons in U 3 Ni 3 Sn 4 .…”
Section: Introductionmentioning
confidence: 99%